A DEIXIS ANALYSIS OF ONLINE NEWSPAPER IN JAKARTA POST - Muchamad Rizal Febriza (IKIP Siliwangi, 2020)
Deixis can be found in the spoken and written media. The use of proffer deixis concepts in the Newspaper media is influenced by background in its topic. This study aims to identify the deixis used in online Newspaper; Jakarta Post. This study was conducted by using the descriptive qualitative method and there are three steps to analyzing this article, 1). read the article, 2). found the deixis, 3). classified the types of deixis proposed by Alan Cruse (2000) theory. The result of a deixis analysis in an online Newspaper found 928 words such as; 70% person deixis, 12% temporal deixis, 10% discourse deixis, 5% social deixis, and 3% spatial deixis. Person deixis is a type of deixis dominantly used in this online newspaperKeywords: Deixis, Online Newspaper, Pragmatics